Fungal association with sessile marine invertebrates - Yarden, Oded (Frontiers in Microbiology, 2014)
The presence and association of fungi with sessile marine animals such as coral and sponges has been well established, yet information on the extent of diversity of the associated fungi is still in its infancy. Culture- as well as metagenomic- and transcriptomic-based analyses have shown that fungal presence in association with these animals can be dynamic and can include “core” residents as well as shifts in fungal communities. Evidence for detrimental and beneficial interactions between fungi and their marine hosts is accumulating and current challenges include the elucidation of the chemical and cellular crosstalk between fungi and their associates within the holobionts. The ecological function of fungi in association with sessile marine animals is complex and is founded on a combination of factors such as fungal origin, host health, environmental conditions and the presence of other resident or invasive microorganisms in the host. Based on evidence from the much more studied terrestrial systems, the evaluation of marine animal-fungal symbioses under varying environmental conditions may well prove to be critical in predicting ecosystem response to global change, including effects on the health of sessile marine animals.